Estudio de factores internos y externos que afectan los niveles de ventas de la empresa Indumot S.A de la ciudad de Babahoyo - Franco Rabasco, Jaime Enrique (2017)
Ecuador in recent years has undergone changes in its economy, which have affected the industrial market, being understood as a secondary sector in the economy, the industry is the transformation of the raw material into products such as motorcycles, cars, furniture, desks , machinery among others. One of the industries we will mention is the company Indumot S.A is an organization that has gradually gained territory in the country becoming one of the largest and largest import and marketing companies of motorcycles and power products in the country; owner of the Honda brand in Ecuador